TARIKAN KENDARAAN PADA KAMPUS UNIVERSITAS BATANGHARI - Ishak Ishak (Jurnal Civronlit Unbari, 2016)
University Batang previously was a development of the High School of Teacher Training and Education. A strong desire from the public to the availability of higher education institutions in a wider spectrum, then on 1 November 1985 was officially stood Batang University. Currently the University of Batanghari parenting 5 faculties with 16 programs of study, comprising 13 courses Strata (S-1), 2 Program Level Education Strata two (S-2) and 1 Study Program Level Education Diploma three (D-3 ). Until the year 2013/2014 the number of graduates (Alumni) until graduation 35 in June 2014 as many as 8771 people. Students will create attraction and great traffic generation.The results of research in the field showed that for the expenditures of the students had no significant effect on the vehicle pull to the campus of the University Batang (sig> 0.05), while the frequency factor visit new students to campus gained significant effect equation Y = 2.78 + 0.85 X2 and also the distance factor to the equation Y = 1.26 + 1.32 X2 X3